Gaelic in Scotland policies, movements, ideologies - McLeod, Wilson (Edinburgh University Press, 2020)
The first comprehensive study of Gaelic in modern Scotland, from 1872 to the presentThe first comprehensive study of the changing role of Gaelic in modern ScotlandExamines changing government policies towards Gaelic and the movements and activists that have campaigned for the languageAssesses shifting ideologies, assumptions, arguments and discourses relating to GaelicDraws on diverse source material with an interdisciplinary approachIn this extensive study of the changing role of Gaelic in modern Scotland - from the introduction of state education in 1872 up to the present day - Wilson McLeod looks at the policies of government and the work of activists and campaigners who have sought to maintain and promote Gaelic. In addition, he scrutinises the competing ideologies that have driven the decline, marginalisation and subsequent revitalisation of the language.Taking an interdisciplinary approach, at the boundary of history, law, language policy and sociolinguistics, the book draws upon a wide range of sources in both English and Gaelic to consider in detail the development of the language policy regime for Gaelic that was developed between 1975 and 1989. It examines the campaign for the Gaelic Language (Scotland) Act 2005, its contents and implementation; and assesses the development and delivery of development and delivery of Gaelic education and media from the late 1980s to the present